The sports cardiology team: personalising athlete care through a comprehensive, multidisciplinary approach. (11th May 2022) - Van Hattum, J; Verwijs, SM; De Vries, ST; Boekholdt, SM; Groenink, M; Van Randen, A; Panhuyzen-Goedkoop, NM; Willems, AR; Knobbe, I; Blom, NA; Van Der Crabben, SN; Bijsterveld, NR; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): Dutch National Olympic Committee & National Sports Federation (NOC*NSF)Amsterdam Movement Sciences (AMS) Background/Introduction: Multidisciplinary teams (MDTs) are an integral part of cardiology. In sports cardiology, multidisciplinary expertise is required to differentiate between extraordinary pathophysiological adaption and pathology. In addition, expert consensus-based sports advice should be prescribed with care considering the potential severe impact on (professional) sports careers. A formally organised sports cardiology MDT could potentially improve quality of care; we therefore established a formally organised sports cardiology MDT at the Amsterdam UMC in April 2019, aiming to facilitate the diagnostic process, enhance the process of formulating optimal sports advice, and to maximise safety in sports. However, no studies have reported on the effects of such teams. Purpose: To systematically investigate and document infrastructure, practices, recommendations, and clinical consequences of a sports cardiology MDT. Methods: We retrospectively analysed all reviewed athletes of our (online) bimonthly sports cardiology MDT meetings (April 2019 to January 2021). The MDT consisted of a permanent panel of experts in sports cardiology, sports- and exercise medicine, cardio/clinical genetics, paediatric cardiology, cardiovascular imaging, and electrophysiology (Figure 1). Cases were referred (inter)nationally by sports physicians or cardiologists. The primary objective of this study was to investigate the 2 years of experiences of practices, recommendations, and clinical consequences of a formal sports cardiology MDT. Results: In total 115 athletes underwent MDT review, mean age 32 (SD 16.0) years, 11% women, 65% recreational athletes, and 54% performed 'mixed' type of sports. MDT review led to diagnosis revision of 'suspected cardiac pathology' to 'no cardiac pathology' in 44/115 (38%) (Figure 2) and increased the number of definitive diagnoses; 77/115 before to 109/115 after MDT review (P<0.05). We observed less 'total sports restrictions' (6 to 0 p<0.05) and more tailored sports advice concerning 'no peak load/specific maximum load' (10 to 26 p<0.05) (Figure 2). At 14 (± 6) months follow-up, 112 (97%) athletes reported no cardiovascular events, 111 (97%) no (new) cardiac symptoms, 113 (98%) adherence to MDT sports advice, and no diagnoses were revised. Conclusion: Our experiences with a comprehensive sports cardiology MDT demonstrate that this approach leads to a higher percentage of definitive diagnoses and fewer diagnosis of cardiac pathology, more tailored treatment- and sports advice, high rates of sports advice adherence, and less total sports restrictions. Our findings highlight the added value of dedicated sports cardiology MDTs in care for elite, professional, and recreational athletes and patients who wish to engage in sports and exercise.